PENGARUH INTENSITAS ASET TETAP, INTENSITAS PERSEDIAAN, DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP MANAJEMEN PAJAK - Ika Riyadah (JEKOS (Jurnal Ekonomi Dan Sosial), 2026)
This study aims to examine the effect of fixed asset intensity, inventory intensity, and corporate social responsibility disclosure on tax management in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The method employed in this study is quantitative, using multiple linear regression analysis. The findings indicate that only the variable of fixed asset intensity has a significant effect on tax management. In contrast, inventory intensity does not have a significant effect, and corporate social responsibility disclosure also shows no effect on tax management.   Keywords : tax management, fixed asset intensity, inventory intensity, corporate social responsibility                                  disclosure